METHODS OF INTELLIGENCE SERVICES IN THE FIGHT AGAINST TERRORISM - Trbojević, Milovan; Svirčević, Branislav (The Policy of National Security, 2023)
Adequate analysis of the struggle of intelligence services against terrorist organizations requires an approach based on the methods and means of action of intelligence institutions. Terrorism is among the most represented security threats in the media and in public discourse. The increasing brutality of terrorist groups and organizations, the frequent mention in the public and the virality of terrorist acts on social networks have led to the creation of a specific fear of terrorism, which is why early detection and stopping of terrorist activities is extremely important. In the field of preventive action against terrorism, intelligence institutions play the most important role. Intelligence institutions primarily use specific methods and techniques for collecting data on terrorist threats, which enables their detection and interception. In addition, intelligence institutions also use non-intelligence methods of combat that require special analysis. On the other hand, terrorist organizations, in addition to carrying out terrorist acts, also carry out activities aimed at disrupting and disavowing intelligence institutions, which further complicates the fight against terrorism.